Homologie de Hochschild Et Espaces Algébriques - Banerjee, Abhishek (MATHEMATICA SCANDINAVICA, 2016)
The purpose of this article is to define the Hochschild and cyclic homologies of an algebraic space X. We consider two definitions of Hochschild homology of X and show that these definitions coincide in the case of a separated algebraic space. Moreover, we construct a shuffle product on the Hochschild homologies of X. Finally, we show that one has a pairing between the Hochschild homologies and cohomologies of X. Résumé Le but de cet article est de définir les homologies de Hochschild et les homologies cycliques d’un espace algébrique X. Nous considérons deux définitions de l’homologie de Hochschild et nous montrons que ces définitions sont les mêmes en cas d’un espace algébrique séparé. De plus, nous construisons un produit shuffle sur les homologies de Hochschild de X. Enfin, nous montrons qu’on a un appariement entre les homologies et les cohomologies de Hochschild de X.